Hierarchization and contextual information management for performing collaborative tasks in land mobile robots - Barbosa, Alexander Silva (2022)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2022.